Investigation of attention, concentration and mental toughness properties in tennis, table tennis, and badminton athletes - Bastug, G.; Sitki, M. (The Sport Journal, 2018)
The aim is to examine the attention, concentration, and mental toughness characteristics of tennis, table tennis, and badminton athletes. A total of 61 athletes participated in the study, with a mean age of 21.18 ± 2.96, playing tennis, table tennis, and badminton. The Concentration Endurance Test (d2 attention test) developed by Brickenkamp (1966) was used to determine the level of attention of the athletes participating in the study. The Letter Cancellation Task, developed by Kumar and Telles (2009), was used to determine the concentration level, and Sheard et al. (2009) developed the "Sports Mental Toughness Questionnaire-SMTQ-14". In the Analysis of Data, the ANOVA test was used to identify differences between groups, and Tukey Honest Significant Difference (HSD) analysis was used to determine which branches were different. As a result; concentration performance was significantly different between the groups. It was determined that tennis athletes were more successful in concentration performance than table tennis and badminton athletes.